Composite reinforced concrete - Taylor, Roy, 1926- (Thomas Telford, 1979)
This monograph is published with the intention of stimulating exploration of this proposed method of construction. It covers in four chapters - simply supported beams; problems of continuity; problems of shear; and miscellaneous problems. It concludes with a summary and conclusions.